SENI SEBAGAI EKSPRESI PROFETIK - Kholid Mawardi (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article reveals the art in Islam which still becomes controversy.This paper describes that art is the form of God in this universe. Inthis context, prophetic art is an art which is based on the effort of releasinghuman from the bad condition of belief, science, knowledge and badcharacter of human. Art is also used for protecting from the ignored things.The prophet’s art itself consists of six points, (1) religion, (2) ethics, (3)aesthetics, (4) intelligence, (5) social sense, and (6) self being. Those feelingssupport man to build his culture, thus art can be used as the culturestrategy to build the society.